DEVELOPING MICROCONTROLLER BASED KINEMATICAL EXPERIMENT SET - Bambang Subali; Agung Wibowo; Sunarno Sunarno; Wawan Kurniawan (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This study was aimed at developing two sets of kinematics experiment namely free fall motion and microcontroller based projectil motion. This study used an R D research design that involves descriptive and evaluative methods. This research was conducted at the Physics Laboratory of Semarang State University and the Science Laboratory Semarang. The stages of this research included design design, tool making, tool validity testing, data retrieval and data processing. Validity test was done to validate the feasibility of the tool by an expert in physics and tested to physics students. A limited scale test and a large scale test were also be done in this study.These tests were conducted to determine the level of readability of the tool and the level of appropriateness of the equipment. This study produced a microcontroller-based experimental set that was feasible for free fall motion and projectile motion experiments. Time measurement results by the kinematics experiment set for free fall motion and projectile motion obtained a better level of accuracy than the previous tool that is equal to 98.30% and has an accuracy level of 99.99%.